Between couch and piano - Rose, J. Gilbert (Hove Brunner-Routledge, 2004)
Why and how do music and abstract art pack such universal appeal? Why do they often have 'therapeutic' efficacy?Between Couch and Piano links well-established psychoanalytic ideas with historical and neurological theory to help us begin to understand some of the reasons behind music's ubiquity and power.Drawing on new psychoanalytic understanding as well as advances in neuroscience, this book sheds light on the role of the arts as stimulus, and as a key to creative awareness. Subjects covered include:* music in relation to the trauma of loss* music in connection with wholeness and the sense of identity* the ability of music to jump-start normal feelings, motion and identity where these have been seemingly destroyed by neurological disease* the theory of therapeutic efficacy of music and art.Between Couch and Piano is a comprehensive overview that will be of interest to all those intrigued by the interrelation of psychoanalysis and the creative arts.